2014
DOI: 10.1002/stem.1761
|View full text |Cite
|
Sign up to set email alerts
|

Elevated O-GlcNAc Levels Activate Epigenetically Repressed Genes and Delay Mouse ESC Differentiation Without Affecting Naïve to Primed Cell Transition

Abstract: The differentiation of mouse embryonic stem cells (ESCs) is controlled by the interaction of multiple signaling pathways, typically mediated by post‐translational protein modifications. The addition of O‐linked N‐acetylglucosamine (O‐GlcNAc) to serine and threonine residues of nuclear and cytoplasmic proteins is one such modification (O‐GlcNAcylation), whose function in ESCs is only now beginning to be elucidated. Here, we demonstrate that the specific inhibition of O‐GlcNAc hydrolase (Oga) causes increased le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 46 publications
5
52
1
Order By: Relevance
“…Our findings differ from those of some groups that reported that O -GlcNAcylation of pluripotency or cell cycle regulatory factors stimulates proliferation or pluripotency and inhibits differentiation of ESC12131436. We found that exogenous GlcN only stimulated proliferation of LG-ESC and did not stimulate pluripotency nor inhibit differentiation, and, while GlcN did increase total protein O -GlcNAcylation, stimulation of proliferation was not due to increased O -GlcNAcylation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings differ from those of some groups that reported that O -GlcNAcylation of pluripotency or cell cycle regulatory factors stimulates proliferation or pluripotency and inhibits differentiation of ESC12131436. We found that exogenous GlcN only stimulated proliferation of LG-ESC and did not stimulate pluripotency nor inhibit differentiation, and, while GlcN did increase total protein O -GlcNAcylation, stimulation of proliferation was not due to increased O -GlcNAcylation.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, as previously mentioned, HBP couples macromolecular metabolism to O-GlcNAc modifications in proteins, including epigenetic modifiers (Figure 3) (94). Cycling of these posttranslational modifications by OGT and OGA are required for naïve and primed state induction, maintenance, and differentiation (95,96). OGT interacts with TET1 enzymes preferentially at transcription start sites, thereby influencing gene expression (58).…”
Section: Metabolism and The Naïve Psc Epigenomementioning
confidence: 98%
“…9,2022 Liu et al reported higher levels of O-GlcNAc, OGT, and OGA in neurons compared to non-neuronal cells in the rat brain. 23 Maintaining high levels of O-GlcNAcylation prevents ectodermal differentiation of mouse ESCs, 13 impairs axonal branching, 24 and inhibits proteasome function. 25 A recent study using human embryonic stem cells (hESCs) found that excess O-GlcNAc decreased the expression of neural markers PAX6 and SOX1.…”
mentioning
confidence: 99%